Radiographic clearance of chronic subdural hematomas after middle meningeal artery embolization. (6th December 2021) - Catapano, Joshua S; Ducruet, Andrew F; Srinivasan, Visish M; Rumalla, Kavelin; Nguyen, Candice L; Rutledge, Caleb; Cole, Tyler S; Baranoski, Jacob F; Lawton, Michael T; Jadhav, Ashutosh P; Albuquerque, Felipe C
Abstract : Background: Few reports discuss variables associated with improved outcomes after middle meningeal artery (MMA) embolization for chronic subdural hematomas (cSDHs). We analyzed radiographic evidence of cSDH clearance after MMA embolization to elucidate optimal techniques, hematoma clearance rates, and suitable length of follow-up. Methods: Patients who underwent MMA embolization for cSDH from January 1, 2018 through December 31, 2020 were analyzed. Patient characteristics, demographics, and technical procedural details were examined. Outcomes for cSDHs analyzed included complete or near-complete resolution at 30, 90, and 180 days following embolization. A multivariable logistic regression analysis identified variables predictive of rapid clearance and resolution of hematomas at 90 days. Results: The study cohort comprised 66 patients with 84 treated cSDHs. The mean (SD) cSDH size differed significantly at 30-day (8.8 (4.3) mm), 90-day (3.4 (3.0) mm), and 180-day (1.0 (1.7) mm) follow-up (p<0.001). More cSDHs had complete or near-complete resolution at 180 days (92%, 67/73) than at 90 (63%, 45/72) and 30 days (18%, 15/84) post-embolization (p<0.001). Only distal embolysate penetration was independently associated with rapid clearance (OR 3.9, 95% CI 1.4 to 11.1; p=0.01) and resolution of cSDHs at 90 days (OR 5.0, 95% CI 1.7 to 14.6; p=0.003). Conclusion: Although 63% of cSDHs with MMA embolization had complete or near-complete resolution by 90 days post-procedure, 92% reached this stage by 180 days. Therefore, 90-day follow-up may be insufficient to determine the effectiveness of MMA embolization for cSDHs, particularly compared with surgical evacuation alone. Also, distal MMA penetration may be associated with more rapid hematoma clearance.